Technical note: Atlas‐based Auto‐segmentation of masticatory muscles for head and neck cancer radiotherapy. Issue 10 (25th August 2020) - Zhang, Xiangguo; Chen, Haihui; Chen, Wen; Dyer, Brandon A.; Chen, Quan; Benedict, Stanley H.; Rao, Shyam; Rong, Yi
Abstract: Purpose: The study aimed to use quantitative geometric and dosimetric metrics to assess the accuracy of atlas‐based auto‐segmentation of masticatory muscles (MMs) compared to manual drawn contours for head and neck cancer (HNC) radiotherapy (RT). Materials and methods: Fifty‐eight patients with HNC treated with RT were analyzed. Paired MMs (masseter, temporalis, and medial and lateral pterygoids) were manually delineated on planning computed tomography (CT) images for all patients. Twenty‐nine patients were used to generate the MM atlas. Using this atlas, automatic segmentation of the MMs was performed for the remaining 29 patients without manual correction. Auto‐segmentation accuracy for MMs was compared using dice similarity coefficients (DSCs), Hausdorff distance (HD), HD95, and variation in the center of mass (∆COM). The dosimetric impact on MMs was calculated (∆dose) using dosimetric parameters (D99%, D95%, D50%, and D1%), and compared with the geometric indices to test correlation. Results: DSCmean ranges from 0.79 ± 0.04 to 0.85 ± 0.04, HDmean from 0.43 ± 0.08 to 0.82 ± 0.26 cm, HD95mean from 0.32 ± 0.08 to 0.42 ± 0.16 cm, and ∆COMmean from 0.18 ± 0.11 to 0.33 ± 0.23 cm. The mean MM volume difference was < 15%. The correlation coefficient (r) of geometric and dosimetric indices for the four MMs ranges between −0.456 and 0.300. Conclusions: Atlas‐based auto‐segmentation for masticatory muscles provides geometrically accurate contours compared to manual drawn contours. Dose obtained from those auto‐segmented contours is comparable to that from manual drawn contours. Atlas‐based auto‐segmentation strategy for MM in HN radiotherapy is readily availalbe for clinical implementation.